The effect of focused and comprehensive written corrective feedback on writing accuracy: a comparative study - Iqbal, Arshad; Saad, Mohammad Azannee (UPSI Press, 2023)
Although a vast body of research has investigated the effectiveness of written corrective feedback on students’ writing accuracy, there is relatively fewer studies that compared the effectiveness of focused and comprehensive written corrective feedback. Determining the relative efficacy of feedback focus is crucial for writing instruction as it can make error correction less tedious for the teacher and more manageable for the learner. Writing teachers need to know whether students can better internalize a selected number of error categories at a time or cope with feedback provided on all errors simultaneously. This research reports a quantitative study that compared the effectiveness of focused and comprehensive corrective feedback on Saudi Arabia English as a Foreign Language (EFL)learners’ essay writing accuracy. Written essays were collected from 18 Foundation Year, Health Sciences students where they were divided into two experimental groups (N=6) and one control group (N=6). A pre-test, post-test, and delayed post-test design was employed to measure the effects of the two types of written corrective feedback on learners’ writing accuracy. The results showed that focused written corrective feedback was not significantly more effective than comprehensive written corrective feedback although it caused lower error means on both the selected error categories as well as on total errors. The results suggest that students and teachers need not view the two types of feedback as mutually exclusive as far as their relative effectiveness is concerned.